A pregação ao serviço da revolução : o Porto e a instauração do liberalismo num sermão de Fr. António de Santa Bárbara - Tavares, Pedro Vilas Boas (2013)
The document which the author presents here - Relação da solemme Acção de graças que o Corpo do Commercio da Cidade do Porto ordenou se rendesse ao Altissimo no dia 22 de Outubro, pela feliz uniao do Supremo Governo do Reino com o Governo Interino de Lisboa (Coimbra, 1821) - is the starting point for a discussion of the causes, main ideas and objectives of the liberal revolution in Oporto in 1820. They are also mirrored in the text of Fr. Antonio de Santa Barbara's commemorative sermon, analysed as an instrument of theoretical justification of the revolution, of indoctrination and of propaganda.